PENGARUH PAJAK EFEKTIF, PROFITABILITAS, DAN UKURAN PERUSAHAAN TERHADAP STRATEGI INCOME SMOOTHING - Adrita gulo; Iren Meita (STKIP Subang, 2026)
This study aims to examine the effect of effective tax rate (ETR), profitability (ROA), and firm size (SIZE) on income smoothing practices in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. Based on agency theory (Jensen & Meckling, 1976) and signaling theory (Spence, 1973), this study uses a quantitative approach with multiple linear regression analysis on a sample of 24 manufacturing companies (69 observations) selected through a purposive sampling method. The Eckel Index is used to measure income smoothing as the dependent variable. The results show that effective tax rate and profitability each have a positive and significant effect on income smoothing, while firm size has no significant effect partially. Simultaneously, all three independent variables have a significant effect on income smoothing, with an Adjusted R² of 14.8%. These findings indicate that fiscal pressure and high profitability are the main drivers of income smoothing behavior in the Indonesian manufacturing sector. This study contributes to the literature by providing empirical evidence on the multifactorial determinants of income smoothing during the post-pandemic economic recovery period.